Unravelling the bioactive potential: Phytochemical and antimicrobial potential of leaf and bark extracts of Pterocarpus dalbergioides Roxb. ex DC. (Andaman Padauk) - Hemalatha, P; Ramadevi, V; Karthikeyan, M; Santhanakrishnan, V P; Krishnamoorthi, S; Jaisankar, I; Saraswathi, T; Ravi, R (Plant Science Today, 2025)
Therapeutic herbs are recognized as valuable sources of bioactives that are utilized in pharmaceutical research. Pterocarpus dalbergioides Roxb. ex DC., commonly called as Andaman padauk or narra, is a medicinal tree endemic to the Andaman Islands, renowned for its therapeutic properties against various health conditions. In this study, phytochemical constituents were quantitatively analysed through Gas Chromatography- Mass Spectrometry (GC-MS) and antibacterial activity was evaluated. The GC-MS analysis indicated a presence of about 100 metabolities with major metabolites including bis(2-ethylhexyl) phthalate, alpha-methyl mannofuranoside, stigmasterol and dotriacontane. The antibacterial assay revealed inhibition zones ranging from 10-13mm and 8-11mm against Staphylococcus aureus, Escherichia coli respectively, with the bark extract of P. dalbergioides while the leaf extract showed inhibition zones of 8-9mm. This pioneering research on the endemic species provides valuable information for further pharmacological research.